Rigidity or fluidity? Does variety-seeking vary based on perceived threat during the COVID-19 pandemic? - Ashrafi, Dewan Mehrab; Chowdhury, S.M. Mukit; Habiba, Wardha; Chowdhury, Shafayat Hossain; Alam, M. Sayeed; Zabeen, Mashruha; Sarker, Md. Atiqur Rahman (National Science Foundation: Colombo, 2024)
The COVID-19 outbreak has significantly changed modern lifestyles and consumption patterns, prompting an increasing focus within consumer behavior research on exploring the impact of perceived threats and the quest for variety. In response to this exigency, our investigation endeavors to ascertain the correlation between the perceived threat posed by the coronavirus and the inclination towards seeking variety. Drawing upon established theoretical frameworks such as reactance theory and terror management theory, we aim to investigate if perceived threat of COVID- 19 heightens individuals’ propensity to seek greater variety in scenarios involving multiple choices. Our initial empirical investigations, conducted across two distinct studies, reveal an evident increase in individual tendency for variety-seeking in both stationery supplies and food items as their perceived threat from the disease intensifies. Furthermore, our third study underscores the nuanced nature of variety-seeking behavior under the influence of perceived threat, highlighting its modulation within predefined decision-making boundaries. Specifically, in situations characterised by heightened perceived threat, consumers exhibit a heightened tendency to seek variety among choices offered by different brands. Conversely, when presented with options within the same brand, their behavior diverges. Notably, this study highlights the intricate interplay between the perceived threat of COVID-19 and alterations in the pursuit of variety.
Keywords: Variety-seeking; COVID-19; Consumer behavior